Effects of Neem-Based Insecticides on Consumption and Utilization of Food in Larvae of Spodoptera eridania (Lepidoptera: Noctuidae). Issue 1 (28th October 2015) - Shannag, Hail K.; Capinera, John L.; Freihat, Nawaf M.
Abstract : Neem-based insecticides, which have many biological properties, were evaluated for effects on growth, food intake, survival, and nutritional indices of Spodoptera eridania (Stoll), an important pest of crops in the western hemisphere. Short-term consumption of food treated with neem-derived insecticides by second-instar larvae resulted in suppressed feeding, retarded weight gain, and prolonged development time after the treated larvae had been transferred to untreated synthetic insect diet. Relative consumption rate, efficiency of conversion of ingested food, relative growth rate, approximate digestibility, and assimilation rate of food were reduced after treatment with neem products, especially by the higher concentrations of neem. Efficiency of conversion of digested food was not affected. Also, application of pure neem oil and Azatrol at high concentrations induced 20 and 13.3% larval mortality, respectively, whereas mortality caused by the lower concentrations of both chemicals did not exceed 3.3%. Larvae of S. eridania were more sensitive to pure neem oil than to Azatrol. These observations may reflect interference of neem with regulation of feeding and metabolism, as well as with anatomy and function of midgut tissues.